(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article is about the fact that the formation of oral speech as a tool of communication for students with hearing impairments is the main goal of a specially organized educational system, and oral speech is a powerful tool for teaching students with hearing impairments, which significantly increases the vocabulary and quality of speech acquisition, as well as the overall level of development of students with hearing impairments.